Psychosocial factors and childhood recurrent abdominal pain. - Boey, Christopher Chiong Meng; Goh, Khean Lee (Blackwell Publishing, 2002)
Recurrent abdominal pain in children is not a single condition but a description of a wide spectrum of clinical manifestations, some of which fit into a definite pattern, such as the irritable bowel syndrome, while others do not. Organic disorders may be present, but in the majority of children they cannot be detected. Although children with recurrent abdominal pain do not generally have psychological or psychiatric illness, there is a growing body of evidence to suggest that psychosocial stress plays an important role in this condition. This review will look into some of this evidence. The precise pathophysiology that results in abdominal pain is still not clearly understood, but the current belief is that visceral hypersensitivity or hyperalgesia and changes in the brain-gut axis linking the central and enteric nervous systems are important mechanisms.